2022
DOI: 10.3389/fcvm.2022.898222
|View full text |Cite
|
Sign up to set email alerts
|

One-Week Dynamic Changes in Cardiac Proteomes After Cardiac Radioablation in Experimental Rat Model

Abstract: BackgroundRecently, stereotactic ablative radiotherapy (SABR) has been adopted to non-invasively treat catheter ablation-refractory ventricular tachycardia (VT). VT episodes have been dramatically reduced after SABR, within weeks; however the underlying mechanisms of these clinical effects and potential mediators of early anti-arrhythmic effect remain unclear.MethodsIn this study, cardiac tissue was harvested from non-irradiated control (0 Gy), conventional irradiated control (2 Gy), and radioablative test (25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Studies on the biological effect of STAR showed: i) cell apoptosis (by detecting cleaved caspase-3 as a marker) in the irradiated volumes three months after treatment but not after six months (18,24), ii) increased expression of connexin 43 (10,11,19,27) and a variety of other proteins (28) and iii) increased gap junctions (11). Moreover, other studies reported: i) clear histological evidence of STAR effect on the target area, found by the loss of myocyte architecture and increased fibrin, vacuoles and calcification (12), and ii) fibrosis in the same area, detected by loss of the smooth cellular organization usually seen in normal AV nodes, extensive fibrin deposition and marked elastosis, but not in the surrounding tissues (21,24,26,30).…”
Section: Resultsmentioning
confidence: 99%
“…Studies on the biological effect of STAR showed: i) cell apoptosis (by detecting cleaved caspase-3 as a marker) in the irradiated volumes three months after treatment but not after six months (18,24), ii) increased expression of connexin 43 (10,11,19,27) and a variety of other proteins (28) and iii) increased gap junctions (11). Moreover, other studies reported: i) clear histological evidence of STAR effect on the target area, found by the loss of myocyte architecture and increased fibrin, vacuoles and calcification (12), and ii) fibrosis in the same area, detected by loss of the smooth cellular organization usually seen in normal AV nodes, extensive fibrin deposition and marked elastosis, but not in the surrounding tissues (21,24,26,30).…”
Section: Resultsmentioning
confidence: 99%
“…34 Hierarchical clustering of the cardiac proteome within 1 week after 25 Gy of X-rays using rats showed significant expression of actin filament proteins. 35 As a response to radiation-induced hyperacute oxidative stress, we can focus on genes and immune activity related to the process of early-stage cardiac remodeling for radiation.…”
Section: Improved Conduction Velocitymentioning
confidence: 99%
“…Compared with traditional differential electrophoresis, proteomics technology based on mass spectrometry has obvious advantages in sensitivity, detection range, high throughput, accuracy, and automation [18]. Therefore, more and more research teams have begun to use proteomics technology for irradiation related research [19,20]. Although the use of SIT to control Lepidoptera pests is theoretically feasible, the mechanism of damage to the reproductive system of P. xylostella via irradiation and the mechanism of how the reproductive system resists different doses of irradiation are still unclear.…”
Section: Introductionmentioning
confidence: 99%